ANALISIS SIKAP KONSUMEN TERHADAP ATRIBUT-ATRIBUT PASAR SWALAYAN DAN PASAR TRADISIONAL: - NOVRITA ANDRIANA FITRI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 1999)
The research was conducted to examine how consumer attitude towardattributes (product, price, location, market design, service, facility) thatoffered by supermarket and traditional market in Kotamadya Yogyakarta.The sample of this research was selected by purposive sampling method.The respondents were visitors and shoppers of both traditional marketand supermarket. The index of consumer attitudes was used to analyzeconsumer attitude. There were several finding of this research. First, generally, positive attitude is shown by consumers to both of traditional market and supermarket eventhough the index value of consumer attitude to supermarket is higher than traditional market. Second, the most important attribut that is considered by consumer is price. The main result indicated that the presence of the supermarket does not influence the traditional market.